Ichthyofauna distribution in downstream region of Opak River, Yogyakarta [Persebaran iktiofauna di bagian hilir Sungai Opak, Yogyakarta] - Djumanto Djumanto; Maria Intan P. Devi; Eko Setyobudi (Jurnal Iktiologi Indonesia, 2013)
Opak River, a river upstream on the slopes of Merapi Mount and empties into Indian Ocean, has a diverse aquatic biotic such as fishes. The aim of this study was to determine the species, abundance, and distribution of fishes in the downstream region of Opak River in Yogyakarta. The length of Opak River was approximately 60 km, the length in upper and downstream region around 30 km each. There were five sampling stations, and the station 1 was located in 5 km away from the river mouth, then followed by station 2 until 5, with the distance between stations around of 4-6 km. Fish sampling was conducted every week from May to June 2012 with six replicates, using electrofishing operated by local fishermen. The result showed that there were 2295 individuals of fishes comprising of 7 orders, 23 families, 30 genera, and 35 species. Of them, there were 26 freshwater species, 5 estuarine species, 3 marine species, and 1 catadromous species. Estuarine and marine species could penetrate into freshwater as far as about 10 km and 5 km from the river mouth, respectively. The most abundant family was Cyprinidae, and the highest individual abundance was Barbonymus sp., followed by Puntius binotatus and Rasbora argyrotaenia. The length distribution among fishes ranged between 2.2 and 36.0 cm, with an average of 9.12 cm. The shortest fish was Sicyopterus longifilis, while the longest was Anguilla marmorata. The weight distribution among fishes ranged from 0.07 to 505.0 g, with an average of 14.9 g. Abstrak Sungai Opak yang berhulu di lereng Gunung Merapi dan bermuara di Samudera Hindia, memiliki biota air yang bera-gam jenis, misalnya ikan. Tujuan penelitian ini adalah untuk menyajikan informasi spesies, kelimpahan, dan distribusi ikan di wilayah hilir Sungai Opak di Yogyakarta. Panjang Sungai Opak sekitar 60 km, panjang di wilayah hulu dan hilir masing-masing sekitar 30 km. Pengambilan contoh ditetapkan sebanyak lima stasiun yang dimulai dari muara, yaitu stasiun 1 terletak 5 km dari muara sungai, kemudian diikuti oleh stasiun 2 sampai 5, dengan jarak antar stasiun sekitar 4-6 km . Pengambilan contoh ikan dilakukan setiap minggu dari Mei hingga Juni 2012 dengan enam ulangan, menggu-nakan alat kejut yang dioperasikan oleh nelayan setempat. Hasil penelitian menunjukkan bahwa jumlah ikan hasil tangkapan diperoleh sebanyak 2295 individu yang berasal dari 7 ordo, 23 famili, 30 genera, dan 35 spesies. Berdasar-kan habitatnya, ada sebanyak 26 spesies air tawar, 5 spesies air payau, 3 spesies air asin , dan 1 spesies katadromus. Spesies ikan air payau mampu bergerak masuk ke sungai yang tawar sejauh 10 km dari muara, sedangkan spesies ikan air asin bergerak sejauh 5 km dari muara. Famili yang memiliki kelimpahan spesies paling banyak adalah Cyprinidae dan kelimpahan individu tertinggi adalah Barbonymus sp. kemudian diikuti oleh Puntius binotatus dan Rasbora argyrotaenia. Distribusi panjang ikan berkisar antara 2,2 dan 36,0 cm, dengan rata-rata 9,12 cm. Ikan terpendek adalah Sicyopterus longifilis, sedangkan terpanjang adalah Anguilla marmorata. Distribusi bobot individu ikan berkisar 0,7505,0 g , dengan rata-rata 14,9 g.